A cellulose nanoarchitectonic: Multifunctional and robust superhydrophobic coating toward rapid and intelligent water-removing purpose. (1st September 2020) - Zhu, Zhaodong; Fu, Shiyu; Basta, Altaf Halim
Graphical abstract: Highlights: Construction of nanocellulose-based micro-particles regulated by thermal aggregation strategy. "Dual-fibers + Reinforcing agent" type nanocellulose-based multifunctional superhydrophobic coating design. Coating has intelligent and rapid water-removing performance. Abstract: The present work deals with using thermal aggregation of spray drying to achieve uniform structuring of cellulose nanocrystals (CNC) with carbon nanotubes (CNT), for obtaining rough annular microparticles with hierarchical dual dimensions. The structure and characteristics of CNC are crucial to microparticle assembly and superhydrophobic modification. The polyurethane (PU) was used to enhance the firmness of microparticles, during thermal aggregation. The investigated CNC/CNT/PU microparticles showed excellent separation ability for water-in-oil emulsions. Moreover, an abrasion-resistant superhydrophobic coating that combined fast and intelligent water-removing, electrical-conductive and antibacterial functions was manufactured through simple spray coating, which profited from effective role of CNT in excellent conversion of light to heat, as well as its thermal, electrical conductivity and antibacterial properties.